ຜົນຂອງຫົວມັນຕົ້ນໝັກຕໍ່ປະສິດທິພາບການຈະເລີນເຕີບໂຕຂອງໝູລາດໂດຍການໃຊ້ບອນໝັກ ແລະ ຮໍາ ເປັນອາຫານໝັກ - Manivanh, Nouphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2016)
This project undertook on an examination of the growth performance of growing pigs. The study was done at farm of animal science department of Souphanouvong University, LuangPrabang Province. The experiment was conducted between November 2015 to January 2016. A growth trial was conducted with 12 local pigs (Moo Lat breed) with average 15 kg mean initial live weight in a randomized complete block design (RCBD), with four replications of three treatments as: T1: Rice bran (RB) 50% + Taro silage (TS) 50%; T2: RB 50% + Protein-enriched cassava root (PECR) 50% and T3: RB 50% + TS 25% + PECR 25%. The aim of the study was to determine the effect of protein-enriched cassava root as supplement on Moulat pigs’ performance fed with rice bran and taro silage as basal diets. Fermentation of streamed cassava root with yeast, urea and di-ammonium phosphate (DAP) increased the content of crude protein in the root from 2.5 to 16.5% in DM. There were positive responses in dry matter (DM) intake, live weight gain, feed conversion ratio as the percentage of protein-enriched cassava root (PECR) in the diet was increased 50 and 25%.